THE STUDY OF YOUTH’ HABITS OF USING INFORMATION AND COMMUNICATION TECHNOLOGIES IN CAREER GUIDANCE - Urdziņa-Merca, Indra; Dislere, Vija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
With the increasing use of information and communication technologies (ICT) in different areas of life, the type of communication and socialization among young people is changing. There is a need for an in-depth look at the possibilities for using ICT in career guidance for young people. The purpose of the study is to discover ICT usage habits of 8-12. classroom students. The study was developed in the Latvia University of Agriculture, the Institute of Education and Home Economics within the Master study programme Career Counsellor. 176 students were involved in the study from six comprehensive schools of Jurmala city. The surveys were conducted in 2016 and 2017. The study revealed that young people use ICT mainly as a means of communication and information source. Questionnaire revealed the most used social networks are Youtube, WhatsApp, Instragram and e-Class. Most of the young people are active in social networks several times a day and this communication channel is an appropriate resource for conducing career guidance for the audience of young, both for communication and the exchange of information on education and work opportunities, during classroom lessons and outside. Results of the research could be used by school teachers and school career counsellors.